A family of chiral ionic liquids from the natural pool: Relationships between structure and functional properties and electrochemical enantiodiscrimination tests. (1st March 2019) - Longhi, Mariangela; Arnaboldi, Serena; Husanu, Elena; Grecchi, Sara; Buzzi, Ivo Franco; Cirilli, Roberto; Rizzo, Simona; Chiappe, Cinzia; Mussini, Patrizia Romana; Guazzelli, Lorenzo
Abstract: In spite of the increasing fundamental and practical interest of electrochemistry in ionic liquids (ILs), exploration of chiral ionic liquids (CILs) in view of enantioselective electrochemistry and electroanalysis is surprisingly overdue. In this study a family of chiral ionic liquids (CILs) based on natural chiral building blocks, of easy synthesis, is detailedly characterized in terms of thermal and electrochemical properties, achieving valuable information about structure−property relationships on account of the systematicity of available family terms. Moreover, they are submitted to a series of chiral electroanalysis tests. Cyclic voltammetry in bulk CILs or with CIL as additives in a bulk achiral ionic liquid IL, shows small but statistically significant potential differences for the enantiomers of two quite different chiral probes, an interesting result since enantiodiscrimination in terms of potential differences in chiral voltammetry (more desirable respect to current differences) has been only seldom obtained so far. The present first example of enantioselective voltammetry in CIL media with stereocenters as localized chirality sources also offers an important and so far missing confirmation of the intrinsically superior level of the inherent chirality strategy, recently resulting in larger potential differences with the same protocols implemented in "inherently chiral" ionic liquid media. Furthermore, an alternative transduction mode, based on electrochemical impedance spectroscopy EIS, is proposed to effectively highlight the enantiodiscrimination ability of CIL media in analytical experiments. Graphical abstract: